VD_FINDINFO Décision / 2013 / 813 vom 16. September 2013 - VD Tribunal cantonal (2013)
AVOCAT, HONORAIRES, FAUTE, FRAIS DE LA PROCÉDURE | 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH), 429 al. 1 let. b CPP (CH), 429 al. 1 let. c CPP (CH), 429 al. 2 CPP (CH), 429 CPP (CH), 430 CPP (CH)